Thermal Performance Comparison of Carbonized and Uncarbonized Briquettes Derived from Maize Agricultural Waste - OKAFOR, IZUCHUKWU JOHN; Okorafor, Okore Okay; EZE, Ejike Collins; ONYEMIZE, Uchenna Charles; TSEE, Andrew Ternenge; WILLOUGHBY, Fouad Ayinde; IKECHUKWU, Kingsely Ugonna; OLANREWAJU, John Seye (Journal on Processing and Energy in Agriculture, 2026)
This study presents a comparative evaluation of the thermal performance and combustion characteristics of four biomass briquette samples derived from maize residues: uncarbonized maize cob (Sample A), uncarbonized cob-stalk blend (Sample B), carbonized maize cob (Sample C), and carbonized cob-stalk blend (Sample D). Briquettes were produced using cassava starch as binder and shaped into standardized moulds cylindrical for uncarbonized and cuboidal for carbonized samples. Key performance metrics including density, moisture content, ash content, calorific value, fuel consumption rate, cooking efficiency, and fuel efficiency were analysed using ASTM protocols and empirical equations. Results showed that uncarbonized briquettes exhibited higher calorific values and mass, with Sample A recording the highest energy yield. However, Sample B demonstrated superior cooking efficiency (17.285%) and fuel efficiency (19.765%), coupled with the lowest fuel consumption rate (0.985 kg/hr), indicating optimal combustion dynamics. Carbonized briquettes, particularly Sample D, offered cleaner combustion and competitive fuel efficiency (18.235%) despite slightly lower energy values. These findings suggest that blending maize cob and stalk enhances briquette performance, and that uncarbonized briquettes especially cob-stalk mixtures offer a viable, low-cost solution for household energy needs in rural settings.
Keywords: Biomass briquettes, Carbonization, Maize cob and stalk, cooking efficiency, Fuel efficiency, Renewable energy